Chinese medicinal herbs as potential prodrugs for obesity - Law, Siu Kan; Wang, Yanping; Lu, Xinchen; Au, Dawn Ching Tung; Chow, Wesley Yeuk Lung; Leung, Albert Wing Nang; Xu, Chuanshan (Frontiers in Pharmacology, 2022)
Obesity is a leading worldwide health threat with ever-growing prevalence, it promotes the incidence of various diseases, particularly cardiovascular disease, metabolic syndrome, diabetes, hypertension, and certain cancers. Traditional Chinese Medicine (TCM) has been used to control body weight and treat obesity for thousands of years, Chinese medicinal herbs provide a rich natural source of effective agents against obesity. However, some problems such as complex active ingredients, poor quality control, and unclear therapeutic mechanisms still need to be investigated and resolved. Prodrugs provide a path forward to overcome TCM deficiencies such as absorption, distribution, metabolism, excretion (ADME) properties, and toxicity. This article aimed to review the possible prodrugs from various medicinal plants that demonstrate beneficial effects on obesity and seek to offer insights on prodrug design as well as a solution to the global obesity issues.